2011
DOI: 10.1177/1043659611404423
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Dimensions of Hospital Safety Climate and Psychosocial Risk Factors Among Japanese Nurses

Abstract: Transcultural research using standard psychosocial tools can reveal important and reliable findings if carefully translated and adapted for the host environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 53 publications
(75 reference statements)
3
16
0
2
Order By: Relevance
“…19 The importance of inter-employee support identified during factor analysis in the current study is similar to some Japanese research, 26 where 'supporting one another at work' was identified as a key dimension of hospital safety climate. Again, this is a similar result to that reported during previous safety climate research where managerial dimensions such as having a high priority to protect workers and encouraging staff to be involved with safety matters were highlighted.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…19 The importance of inter-employee support identified during factor analysis in the current study is similar to some Japanese research, 26 where 'supporting one another at work' was identified as a key dimension of hospital safety climate. Again, this is a similar result to that reported during previous safety climate research where managerial dimensions such as having a high priority to protect workers and encouraging staff to be involved with safety matters were highlighted.…”
Section: Discussionsupporting
confidence: 84%
“…19 The internal consistency of our Chinese-language HSCS was even higher than Gershon and colleagues' original Englishlanguage version, where the internal consistency scores ranged from 0.71 to 0.84. With a Cronbach's alpha score of 0.930, our survey instrument demonstrated a very high internal consistency, comparing well with previous safety climate research where Cronbach's alpha scores have been reported to be 0.86 18 and 0.89.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…It has also been suggested that the more psychological demands needed for a particular task, the greater the possibility to develop any kind of musculoskeletal disorder regardless of the anatomical area[45]. Some research from Japan suggests that this may relate to group dynamics, as well as individual factors[46]. Surprisingly, psychosocial factors such as low decision latitude, high job insecurity, low co-worker, low supervisor and low social support, and high job dissatisfaction were not positively associated with development of LBP in the current study.…”
Section: Discussionmentioning
confidence: 99%